Pelatihan Welding dan Pembuatan Standing Pot Bunga pada Siswa Teknik Kendaraan Ringan di Sekolah Menengah Kejuruan - Nurul Burhan; Fuad Abdillah; Budiyanto Budiyanto (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Ivet, 2026)
Welding is an art form that can be applied and applied in craft products. The purpose of this community service activity is to 1) provide students with knowledge about welding techniques, 2) train students' skills in making standing flower pots. The method of implementing the activity is in the form of initial evaluation, demonstration, practice, and final evaluation. The results of the training activities can be concluded that. 1) students' knowledge regarding welding techniques can be concluded that the average before training is 54.75 and after training is 80.25. 2) students' skills are seen from the neatness of welding and the completion of standing flower pot products, of the 20 participants who participated, all of them were able to complete their tasks